COMPARISON OF MEAN ARTERIAL PRESSURE (MAP) CHANGES ON LARYNGEAL MASK AIRWAY INSERTION WITH PROPOFOL AND SEVOFLURANE - Samina Aslam; Robina Firdous; Humaira Ahmad (Journal of University Medical & Dental College, 2014)
ABSTRACT: INTRODUCTION: Stability of Mean Arterial Pressure pre-operatively, during procedure(s) and post-operatively is of great concern to the healthcare practitioners in the field of anesthesia. Laryngeal mask airway (LMA) is considered a secure technique of airway management both in emergency and in elective procedures. Among several practices of LMA insertion, Propofol i.v. and Sevoflurane inhalation induction are most favorite and commonly used. OBJECTIVES: To study the Mean Arterial pressure stability in patients receiving sevoflurane inhalational induction for LMA insertion in comparison with the patients undergoing LMA insertion with propofol intravenous induction of anesthesia. STUDY DESIGN: Randomized controlled trial. SETTING AND DURATION: Department of anesthesia and intensive care Allied Hospital Faisalabad. Study was carried out over a period of six months from 28-05-2012 to 28-11- 2012. SAMPLE SIZE: 90 patients (45 patients in each group i.e. receiving Propofol or Sevoflurane). MATERIALS AND METHODS: A total of 90 patients (45 patients in each group) ranging from the age of 18 years to 34 years were included in this study. Sample population includes patients with a random set of surgical needs. In group A, patients were given propofol i.v. induction for a variety of surgical procedures and in group B, patients were anesthetized using sevoflurane induction again for a random set of surgical procedures. RESULTS: Mean age of patients in Group A was 25.78 and 25.27 in Group B. Frequency of patients according to ASA status was 35 ASA-l and 10 ASA-ll in Group A and 30 and 15 in Group B respectively. Mean Arterial Pressure dropped in 15 patients (33.3%) of Group-A and 3 patients (6.6%) in group B. CONCLUSION: In this study, it was found that sevoflurane inhalational induction for LMA insertion is associated with stable Mean Arterial pressure, and therefore, valuable.